Idiopathic Granulomatous Mastitis- Challenges of Diagnosis and Treatment (Medicine Today, 2017)
Idiopathic Granulomatous Mastitis (IGM) is a benign breast disease. Owing to its unknown aetiology, rareness,variation of presentation - diagnosis and treatment is still a challenge. This is a retrospective review of clinical presentation and investigation finding of all patients histopathologically diagnosed as IGM from February 2010 to January 2014. Treatment outcome and follow up information were recorded. 6(42%) patient presented with breast abscess, 5(35.7%) patient had features of mastitis without abscess, 3(21.4%) patient had painful firm to hard lump. Diagnosis confirmed by excisional/ incisional biopsy. 9(64%) patients needed more than one surgical intervention. Mean follow up period was 27months. Standardization and optimization of treatment is yet to be achieved.Medicine Today 2016 Vol.28(1): 14-16